PingTV: a case study in visual network monitoring - Gubin, Alexander; Yurcik, William; Brumbaugh, Larry (Proceedings of the conference on Visualization '01, 2001)
PingTV generates a logical map of a network that is used as an overlay on a physical geographical image of the location from the user perspective (buildings, floors within buildings, etc.). PingTV is used at Illinois State University as a visualization tool to communicate real-time network conditions to the university community via a dedicated channel on the campus cable TV system. Colored symbols allow students and staff to discern high-congestion "rush hours" and understand why their specific Internet connectivity is "broken" from the wide range of potential causes. Lessons learned include the use of color to visually convey confidence intervals using color shading and the visualization of cyclical network traffic patterns. Our implementation is general and flexible with potential for application for other domains.